Contribution of Forest Farmer Groups in Land Management through the Agroforestry System - Sasmita, Shafira Dita; Nakayama, Hitomi (JCIC : Jurnal CIC Lembaga Riset dan Konsultan Sosial, 2025)
This study analyzes the contribution of Forest Farmer Groups (KTH) in land management through agroforestry systems in two schemes, namely Social Forestry and Non-Social Forestry. Using a descriptive qualitative approach, data was collected through field observations, in-depth door-to-door interviews, and documentation of 29 members of the Ajisaka KTH, 67 members of the Tanjungjaya KTH, and 25 members of the Bunter KTH. The results of the study show that agroforestry has become an alternative livelihood strategy through crop diversification, such as corn, cassava, bananas, ginger, turmeric, and coffee, which are planted among teak trees managed by Perhutani and PTPN. In the Ajisaka KTH, which operates under the Social Forestry scheme, legal access and institutional recognition strengthen collective awareness, community solidarity, and provide additional income, although agriculture is still considered a side business. Meanwhile, KTH Tanjungjaya and Bunter, which lack strong legal standing, are more vulnerable but demonstrate adaptive strategies through profit-sharing systems, wage systems, and additional ventures such as balsa seedling production and honeybee farming. Both schemes demonstrate that agroforestry not only increases household income but also strengthens food security, social empowerment, and ecological sustainability. Thus, agroforestry is not merely an agricultural technique but a socio-economic tool capable of balancing livelihood needs and environmental conservation.